Effect of Forbrain Cognitive Training Intervention Prescriptions Based on Risk Factors on Patients with Cognitive Impairment After Traumatic Brain Injury - ZHANG Xueru; WANG Hongbin; CUI Huiying; HAO Xijun; CHEN Changxiang (康复学报)
ObjectiveTo observe the effect of Forbrain cognitive training intervention prescriptions based on risk factors on cognitive function and activities of daily living in patients with cognitive impairment after traumatic brain injury (TBI).MethodsA total of 120 patients with cognitive impairment after TBI treated in Tangshan Workers' Hospital from October 2021 to May 2022 were randomly divided into control group, observation group 1 and observation group 2 according to Excel random function, with 40 cases in each group. During the intervention, 3, 1, 1 cases dropped out respectively in the control group, observation group 1 and observation group 2, and 37, 39 and 39 cases were finally included in the three groups respectively. The control group received neurosurgical routine nursing care; the observation group 1 received Forbrain cognitive training (reading training was encouraged) in addition to the routine care; the observation group 2 received the Forbrain cognitive training intervention prescriptions based on the risk factors of cognitive dysfunction (insomnia, headache, depression, low social support and upper limb motor dysfunction) in addition to the routine care. For all of the three groups, the interventions were provided for 20 minutes a time, twice a day, lasting for two weeks. Before and after intervention, the Loeweistein Occupational Therapy Cognitive Assessment (LOTCA)-Ⅱ was used to evaluate the patients' cognitive function; Barthel Index (BI) was used to evaluate the activities of daily living ability of patients.Results(1) Cognitive function: compared with that before treatment, the total score of LOTCA-Ⅱ in the observation group 1 and the observation group 2 were higher after intervention, and the differences were statistically significant (P<0.05); compared with the control group, the scores of praxis and attention in the observation group 1 after intervention were significantly higher, and the scores of visual perception, action application score, visual movement organization time score, operation of thinking score, concentration score and LOTCA-Ⅱ total scores in the observation group 2 after intervention were significantly higher, and the differences were statistically significant (P<0.05). Compared with the observation group 1, the visual and sensory scores and LOTCA-Ⅱ total scores of the observation group 2 after intervention were significantly higher, and the differences were statistically significant (P<0.05). (2) Activities of daily living: compared with that before intervention, BI score in the observation group 1 and the observation group 2 were significantly higher after intervention, and the differences were statistically significant (P<0.05). Compared with the control group and the observation group 1, the BI score of the observation group 2 after intervention was significantly higher, and the difference was statistically significant (P<0.05).ConclusionThe Forbrain cognitive training intervention prescriptions based on risk factors can improve the cognitive function and activities of daily living of TBI patients, which is recommended in clinical practice.